2020
DOI: 10.1093/jpepsy/jsaa009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Health Literacy in Childhood Cancer Patients, Survivors, and Their Caregivers

Abstract: Objective This systematic review examined the literature regarding health literacy among pediatric cancer patients, survivors, and their caregivers. Specific aims were to identify and summarize measures used, levels of and demographic correlates of health literacy, effects of health literacy interventions, and associations between health literacy and health outcomes. Methods The search strategy was executed in the following d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
8
0
3
Order By: Relevance
“…Several studies in Western countries have revealed that a younger age at diagnosis, a lower socioeconomic status (SES) and the specific cancer type are the major factors influencing health literacy among survivors and caregivers. 12 , 13 However, these risk factors may not be generalizable to the Asian population due to differences in cultural, lifestyle and health practices. 14 To date, no study has evaluated the cancer‐specific knowledge held by survivors of childhood cancer in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in Western countries have revealed that a younger age at diagnosis, a lower socioeconomic status (SES) and the specific cancer type are the major factors influencing health literacy among survivors and caregivers. 12 , 13 However, these risk factors may not be generalizable to the Asian population due to differences in cultural, lifestyle and health practices. 14 To date, no study has evaluated the cancer‐specific knowledge held by survivors of childhood cancer in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation and stress have also been shown to affect one's ability to comprehend health information, negatively impacting health literacy (Morrison et al, 2019). Therefore, recalling the components of their child's treatment plan on an open-ended questionnaire may have presented parents with a more challenging task than required by the other key concept questions, and may have been particularly difficult for parents with low literacy, given that the new diagnosis period is known to be a stressful and emotional time (Rabineau et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently a paucity of literature regarding how low health literacy may affect the ability of parents to learn to care for their child with cancer. Very few studies have assessed health literacy in parents of children with cancer, and among these studies, there is no standardized way that health literacy has been assessed (Lynn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy is especially important for patients with cancer because decisionmaking for prevention, screening, and treatment in the oncology environment is complex. Since parents can directly influence the health literacy needs of children (14,19,20) and clinical outcomes of children are affected by parental health literacy, therefore, promoting health literacy is essential for this group (13).…”
Section: Introductionmentioning
confidence: 99%
“…Results of a study by Yuen et al aimed at designing a conceptual model for health literacy promotion for caregivers of patients with cancer, showed that the health literacy of caregivers is a multi-dimensional concept and includes a wide range of personal and interpersonal elements and is affected by the healthcare system and social factors (24). Other studies revealed that this group still has many ignored needs in terms of health literacy (18,20,23,25).…”
Section: Introductionmentioning
confidence: 99%